2021
DOI: 10.7150/ijms.51439
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of cytotoxicity and induction of apoptosis by cationic nano-liposome formulation of n-butylidenephthalide in breast cancer cells

Abstract: Breast cancer is the second most common malignancy in women. Current clinical therapy for breast cancer has many disadvantages, including metastasis, recurrence, and poor quality of life. Furthermore, it is necessary to find a new therapeutic drug for breast cancer patients to meet clinical demand. n-Butylidenephthalide (BP) is a natural and hydrophobic compound that can inhibit several tumors. However, BP is unstable in aqueous or protein-rich environments, which reduces the activity of BP. Therefore, we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…DTPLNs showed time-and pHdependent drug release, which led to enhanced antitumor effectiveness of MTO and DOX compared to their free forms in MCF-7 and PC-3 tumor cells. Furthermore, Huang et al [165] found that n-butylidenephthalide (BP) suppressed the proliferation of SK-BR-3 colon cancer cells, and BP/LPPC (Lipo-PEG-PEI Complex) increased its cytotoxicity by stabilizing the BP activity in CT-26 colon carcinoma and RAW 264.7 macrophage. By accelerating the efficiency of entrapment to cause cell death and cell cycle arrest, LPPC encapsulation effectively increased BP cytotoxicity.…”
Section: Encapsulation Improves the Efficacy Of Anticancer Drugsmentioning
confidence: 99%
“…DTPLNs showed time-and pHdependent drug release, which led to enhanced antitumor effectiveness of MTO and DOX compared to their free forms in MCF-7 and PC-3 tumor cells. Furthermore, Huang et al [165] found that n-butylidenephthalide (BP) suppressed the proliferation of SK-BR-3 colon cancer cells, and BP/LPPC (Lipo-PEG-PEI Complex) increased its cytotoxicity by stabilizing the BP activity in CT-26 colon carcinoma and RAW 264.7 macrophage. By accelerating the efficiency of entrapment to cause cell death and cell cycle arrest, LPPC encapsulation effectively increased BP cytotoxicity.…”
Section: Encapsulation Improves the Efficacy Of Anticancer Drugsmentioning
confidence: 99%
“…Interestingly, based on the diffusion release exponent values (n), the mechanisms of the ROT release from the PC/Chol/IA-n(OH) and PC/Chol/TPPB-n liposomes were different. The PC/Chol/IA-n(OH) liposomes were characterized by Fickian diffusion (n ˂ 0.45), while for the PC/Chol/TPPB-n liposomes, the The main challenge in the field of cancer treatment is the insufficient selectivity of the systems toward tumor cells [82,83]. Therefore, the next step of the biological activity study was focused on evaluating the cytotoxicity of the ROT-loaded liposomes toward the tumor and normal cell lines in vitro.…”
Section: S2mentioning
confidence: 99%